Building on What We Have Learned A National Dialogue on Standards-Based Education - Biemesderfer, Susan; North Central Regional Educational Lab., Oak Brook, IL.; Berkana Inst., Provo, UT.; Mid-Continent Research for Education and Learning, Aurora, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
Three nonprofit organizations support a dialogue on standards-based educational reform. North Central Regional Education Laboratory, Mid-Continent Research for Education and Learning, and the Berkana Institute offer Web sites and a toll-free number to those who want to comment on this type of reform. In surveys, a clear majority of parents feel that testing to identify students who need help and to publish school's scores for comparison are appropriate uses of standards tests. However, even more parents are against using the score on one test as the criterion for promotion to the next grade or for graduation. In high-stakes assessment, teacher's jobs and students' promotion are at risk. Teachers have to be apprised of the contents of the tests given in order to even attempt to teach to the test. Another major concern is equity. African American, Hispanic, and Native American students tend to perform at lower academic levels than whites and Asian/Pacific Islanders on most standardized measures of achievement. High-stakes testing policies may increase education inequity between whites and minorities or between affluent and impoverished students, perhaps increasing dropout rates. Possibly standards scores will prod schools to target resources where they are needed most. Potential topics to address, suggested questions, and recommendations from research literature are offered, along with a glossary and suggested reading. An appendix traces the history of this type of reform from 1983. (RJK)
Availability: For full text: http://www.nationaldialogue.org.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: ED-01-CO-0011.
Contract Number: ED-01-CO-0006.
ERIC Note: Version 1. The most recent version located online at the National Dialogue Web site.
May also be available online. Address as at 14/8/18
Keywords: Academic Standards; Educational Change; Elementary Secondary Education; Standardized Tests; Berkana Institute -- Mid Continent Research for Education and Learning -- North Central Regional Educational Laboratory; Opinion Papers; Reports, Descriptive